Ketika Giveaway Menjadi Modus Kejahatan: Perlindungan Hukum Korban di Era Digital [When Giveaways Become a Criminal Modus Operandi: Legal Protection for Victims in the Digital Era] - Moh. Azaz Abbas Marzuqi; Subekti Subekti; Fathul Hamdani; Muhammad Yustino Aribawa (UKInstitute, 2026)
The advancement of information technology has facilitated the widespread use of giveaways on social media platforms, which have increasingly been exploited by unscrupulous actors as a form of fraudulent activity. This study examines the legal protection afforded to victims of giveaway-related fraud on social media. Such schemes are commonly perpetrated by impersonating public figures or official accounts to obtain money or personal data from unsuspecting users. From a legal standpoint, these actions constitute the criminal offense of fraud as stipulated in Article 378 of the Indonesian Criminal Code (KUHP) and a violation of Article 28(1) of the Electronic Information and Transactions Law (UU ITE), which prohibits the dissemination of false or misleading information that results in consumer losses in electronic transactions. The findings underscore the necessity of a comprehensive legal approach that extends beyond the punishment of offenders to include preventive strategies, such as strengthening digital platform governance, enhancing public digital literacy, and fostering close coordination among regulatory authorities, including the Financial Services Authority (OJK), Bank Indonesia, and electronic system operators, to support early detection and effective victim recovery. Abstrak. Perkembangan teknologi informasi telah memunculkan fenomena giveaway di media sosial yang kini sering disalahgunakan oleh pihak tidak bertanggung jawab sebagai modus penipuan. Penelitian ini bertujuan untuk menganalisis perlindungan hukum bagi korban penipuan giveaway di media sosial. Praktik penipuan ini biasanya dilakukan dengan memanfaatkan nama tokoh terkenal atau akun resmi untuk meminta sejumlah uang maupun data pribadi korban. Secara hukum, tindakan ini dikualifikasikan sebagai tindak pidana penipuan sebagaimana diatur dalam Pasal 378 KUHP serta pelanggaran terhadap Pasal 28 ayat (1) UU ITE mengenai penyebaran berita bohong yang merugikan konsumen dalam transaksi elektronik. Hasil analisis menunjukkan bahwa diperlukan pendekatan komprehensif yang tidak hanya berfokus pada pemidanaan pelaku, tetapi juga pada aspek pencegahan melalui penguatan tata kelola platform digital, peningkatan literasi digital masyarakat, serta koordinasi yang erat antara otoritas seperti OJK, Bank Indonesia, dan penyelenggara sistem elektronik untuk deteksi dini dan pemulihan korban.